Edge reconstructions of black phosphorene: a global search - Liu, Yue; Li, Da; Cui, Tian (Nanoscale, 2021)
Despite reports of possible edge reconstructions of black phosphorene, the underlying mechanisms that determine the atomic configurations and appearance of black phosphorene edges have not been elucidated to date. In this study, the particle swarm optimization (PSO) algorithm is used to perform a global search of black phosphorene edge structures. In addition to the most stable edges, three databases of the typical black phosphorene zigzag edge, armchair edge, and skewed diagonal edge are constructed for the first time. The local phosphorus concentration plays an important role in determining the edge atomic configurations and the appearance of an edge. Variations in the local phosphorus concentration result in the rearrangement of sp 3 -hybrid bonds or the formation of double bonds that balance the dangling bonds at the edges and stabilize the black phosphorene edges. The black phosphorene edge databases provide a useful reference for edge studies of other 2D materials with puckered honeycomb structures. A global search of black phosphorene edge structures are performed based on the particle swarm optimization algorithm.